O estilo de vida e o envelhecimento de professoras sem filhos/as - Roth, Vanessa Juliane da Silva (2019)
We observed that family configurations have been changing over time, the number of couples and women without children has been increasing, and the aging of the population is growing dizzily in our country. These changes reflect other interests, experiences and lifestyles possible for women who have turned away a strong representation in our culture, the motherhood experience. Thus, we aim to analyze the lifestyle of female teachers without children and their relationship with the aging process. Fifteen teachers participated, among them, 8 taught in Basic Education and 7 in Higher Education, they were between 50 and 67 years old, had no children and live in the city of Santa Maria / RS. The teachers were intentionally selected through the snowball sampling technique. In this qualitative research approved by the Ethics Committee, we conducted semi-structured interviews in depth, which were literally transcribed, and then organized and interpreted based on the content analysis. The results were presented in two articles, the first one aimed to know the trajectories until non-maternity visibilizing the lifestyle of these teachers, discussing the possible changes in the aging process and the relationship between children and care in old age. It was evidenced that, for most of the teachers, motherhood did not occupy the center of their life projects, but rather, the studies and the work did, which generated a freer lifestyle, where the time for themselves is valued, as well as social activities. They consider that children are not and should not be seen as a guarantee of care in old age, but they think that the economic condition is a determining factor to provide higher or lower quality of life at this stage. The second article aimed to know the affectivities and their unfolding in the life of these teachers and to understand their relations with the work and how they deal and / or project their retirements. It was found that most teachers consider that friendships are fundamental in their lives and seek to nurture them, work occupies a privileged space and feeds countless projects to be carried out, while some of the teachers see retirement as something far away, since they want continue to work for a long time, others consider that it represents new opportunities for learning and experiences. Finally, in both studies, there were no strong differences in lifestyles and representations about non-maternity and aging in the comparison between the narratives of Basic Education and Higher Education teachers. The theme of this study is of great relevance because it approaches contemporary issues that involve new social configurations and breaks with stereotypes that point to motherhood as a destination for women, making visible other lifestyles and new projects of aging.